2022
DOI: 10.3390/su14020693
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison between Heat Flow Meter (HFM) and Thermometric (THM) Method for Building Wall Thermal Characterization: Latest Advances and Critical Review

Abstract: It is well-known that on-site measurements are suitable for verifying the actual thermal performance of buildings. Performance assessed in situ, under actual thermal conditions, can substantially vary from the theoretical values. Therefore, experimental measurements are essential for better comprehending the thermal behavior of building components, by applying measurement systems and methods suitable to acquire data related to temperatures, heat flows and air speeds both related to the internal and external en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…A general review of many works in the 2000-2017 period presented typical discrepancies in the range of 20%-30% (Teni et al, 2019). Evangelisti et al (2022) performed a bibliographic research on HFM and THM methods and identified a number of sources of uncertainty and limitations for milder climates. ''Inaccurate installations cause uncertainties ranging from 26% to 30%; poor contacts, 2% to 5%; non-one-dimensional heat flux, 1% to 5%; wall orientation, 37%; moisture up to 71%; and different heights among sensors, 17% to 22%.''…”
Section: State Of the Artmentioning
confidence: 99%
“…A general review of many works in the 2000-2017 period presented typical discrepancies in the range of 20%-30% (Teni et al, 2019). Evangelisti et al (2022) performed a bibliographic research on HFM and THM methods and identified a number of sources of uncertainty and limitations for milder climates. ''Inaccurate installations cause uncertainties ranging from 26% to 30%; poor contacts, 2% to 5%; non-one-dimensional heat flux, 1% to 5%; wall orientation, 37%; moisture up to 71%; and different heights among sensors, 17% to 22%.''…”
Section: State Of the Artmentioning
confidence: 99%
“…Policy measures often limit the U-values of building elements, but when we solve a problem of great importance, it is better to analyze the problem with numerical methods, since dynamic parameters such as heat storage are included in the analysis, so that we can, for example, optimize the thickness of the insulation layer so that we have a larger U-value but better energy efficiency when considered all year round [44]. All results are compared with the U-value defined in this subsection, since the analyzed specimens from the experimental research have known layers and it is common in the literature ( [23,27,33,[45][46][47]) to compare the analyzed solution with the theoretical U-value defined in this way.…”
Section: Theoretical U-valuementioning
confidence: 99%
“…The HFM measurement was continued after 72 h to compare the resulting U-value from the HFM measurement (U HFM ) with the U-value from the heat flux predicted by the deeplearning model (U DL ). Both values were compared with the theoretical U-value according to ISO 6946 (U ISO ) [30], so that the results of this research can be compared with related papers [23,27,33,[45][46][47]. This research methodology is clearly presented in Figure 4.…”
Section: Experimental Setup and Research Designmentioning
confidence: 99%
See 2 more Smart Citations